Comparative Study Of Different Multilevel Topologies Of Five Level Inverter Using Spwm - Ab Ghani, Mohd Ruddin; Nabil, Farah; Mat Lazi, Jurifa; Mohd Amin, Nur Huda; Othman, Syariffah; Jano, Zanariah (Research India Publications, 2016)
This paper proposed a simulation model of three different typologies of five-level inverter. The study investigated three topologies of multilevel inverter namely Flying Capacitor Multilevel Inverter (FCMLI), Diode Clamped Multilevel Inverter (DCMLI) and Cascaded H-bridge Multilevel inverter (CHMLI). These topologies were compared in terms of Total Harmonic Distortion (THD), switching loses and the number of power electronic components being utilized. The simulation result was conducted using MATLAB/SIMULINK. The findings showed that the PWM H-Bridge topology has the lowest total harmonic distortion (THD). In addition, the H-Bridge topology has the lowest switching losses and utilizes less power electronic components.